Dampak Citra Destinasi, Faktor CRM dan Kepuasan Wisatawan Terhadap Loyalitas Wisatawan Gunung Kelud pada Era New Normal - Djunaedi Djunaedi; Fariansyah Hassan Basrie; Angga Rizka Lidiawan; Pamadya Vitasmoro (Islamic University of Kalimantan MAB Banjarmasin, 2022)
The tourism industry has become one of the sectors whose operations have been hampered due to the pandemic. Since the enactment of the new normal in the midst of the COVID-19 pandemic, several tourist attractions have been active again, including the Mount Kelud tourist area located in Kediri Regency. The problem is how the tourism sectors in the Kelud mountain area can regain tourist interest and loyalty after actively operating again. Therefore, the purpose of this paper is to examine the destination image factor, the Customer Relationship Management (CRM) factor which in this case refers to tourists, and tourist satisfaction with tourist loyalty to the Gunung Kelud tourist area, either partially or simultaneously. This research uses multiple linear regression method to 320 respondents. The results of the data distribution statement obtained, amounting to 3.15 which falls into the required scale category. From the modeling results, the regression value of the destination image decreased by 0.57%, customer relationship management increased by 12.1% and satisfaction increased by 30.9%. Partially, the destination image is worth 2,702 units, customer relationship management is 1,982 units and tourist satisfaction is 6,903 units for the loyalty of Mount Kelud tourists. Meanwhile, simultaneously that Destination Image, Customer Relationship Management and Customer Satisfaction are worth 21,402 units.